The way of looking at brings forth new ways of thinking (2012)
In Maria Auxiliadora School, located in Villapinzón municipality, it is proposed a research work based on the principles of image pedagogy – a proposal aiming at the education of sensitivity of students’ way of looking in order to generate critical thinking development, broadening students’ horizons of self-knowledge as subjects of their own environment, of the complex media world around them, and of the globalized world related to that environment. Thus, this paper states the importance of the education of students’ way of looking at aspects that in daily life are overlooked, or that, even worse, are not understood. Then, some reflections concerning image reading, its importance in current society, the vertiginous way in which they develop, the need to integrate and take advantage of images as a knowledge tool and subject, the relevance of education towards analytic reading of implicit messages in the new codes imposed by media, and the overcoming of the dichotomy between text reading and image reading arise.